THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON PURCHASING DECISIONS ON CHATIME SETIA BUDI MEDAN - Irma Br Siregar; Indawati Lestari (RADJA PUBLIKA, 2025)
This article aims to determine the effect of Experiential Value on revisit intention at Waterfront City This study aims to determine the effect of product quality and service quality on purchasing decisions at Chatime Setia Budi, both partially and simultaneously. The research method used is a quantitative approach with a purposive sampling technique, aimed at Chatime Setia Budi consumers who have made purchases. The number of samples was determined as many as 96 respondents. Data analysis techniques used include classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination R²). The results of the study indicate that partially, both product quality and service quality variables have a positive and significant effect on purchasing decisions at Chatime Setia Budi. Simultaneously, both independent variables also have a positive and significant effect on purchasing decisions. Thus, it can be concluded that improving product quality and good service can encourage an increase in consumer purchasing decisions at Chatime Setia Budi.